Evaluation of Heavy Metals and Physicochemical Parameters of Oil-contaminated Soil and Water Samples from Bonny, South-South, Nigeria - E. U. Ezeji; C. O. Anyanwu; N. C. D. Ukwandu (Archives of Current Research International, 2019)
This study analyzed physical, chemical and selected heavy metals concentration of oil-polluted soil and water samples from Bonny, South-South, Nigeria. Unpolluted soil and water samples were used as controls. The pH of the test soil sample was acidic (4.24±0.03) when compared with control (7.6±0.05). Chloride, Phosphorus, Magnesium and Potassium concentrations of the test soil samples were 1151.614±0.37 mg/g, 1.23±0.02 mg/g, 11.27±0.34 mg/g and 11.52±0.5 mg/g respectively. Selected heavy metals such as Iron (Fe), Cadmium (Cd), Mercury (Hg), Arsenic (As), Lead (Pb) and Copper (Cu) showed that Hg and As were below detectable limits in test and control samples while Cd and Pb were below detectable limit in the control sample while test sample had 0.015±0.01 mg/g and 1.73±0.04 mg/g respectively. Fe and Cu contents were high at 38.7±0.13 mg/g and 5.49±0.05 mg/g when compared with the control at 3.52±0.02 mg/g and 1.08±0.03 mg/g. Total Petroleum Hydrocarbon (TPH), Total Organic Carbon (TOC) and Total Organic Matter (TOM) were at 5.93±0.13 mg/g, 3.64±0.1 mg/g and 4.23±0.1 mg/g respectively. Water pH, Temperature, Conductance, Dissolved Oxygen, Biological Oxygen Demand (BOD5) and Turbidity were 5.21±0.03, 25.1±0.01ºC, 610±0.04 µS/cm, 5.0±0.03 mg/l, 1.8±0.02 mg/l, and 53.50±0.06 NTU respectively. Chloride, Phosphorus, Magnesium, Potassium, Calcium and Bicarbonate concentrations of the water were 609.82±0.37 mg/ml, 1.03±0.02 mg/ml, 13.41±0.42 mg/ml, 7.68±0.3 mg/ml, 21.22±0.12 mg/ml and 4.3±0.07 mg/ml in that order. Arsenic and Mercury were below detectable limit in both test and control samples while Fe, Cd, Pb, and Cu were 42.2±0.6 mg/ml, 0.016±0.001 mg/ml, 1.9±0.04 mg/ml and 5.2±0.03 mg/ml respectively. Total Petroleum Hydrocarbon, Total Suspended Solids, Total Dissolved Solids, and Total Solids were 3.87±0.11 mg/ml, 23036±0.51 mg/ml, 396.5±0.3 mg/ml and 23433±0.4 respectively. The levels of detected heavy metals were higher than the World Health Organization (WHO) permissible limits and Nigerian standard set by Federal Environmental Protection Agency (FEPA). This indicates a moderate level of pollution in both soil and water samples, as a result, poses a serious threat to ecological and species survivability as well as growth and reproduction of aquatic and plant life.